2017
DOI: 10.1080/1369183x.2017.1299622
|View full text |Cite
|
Sign up to set email alerts
|

An ‘undeliberate determinacy’? The changing migration strategies of Polish migrants in the UK in times of Brexit

Abstract: This paper reformulates classical questions regarding the plans and strategies of Polish migrants in the UK -such as decisions to leave or remain in the host country, or be 'deliberately indeterminate' about future plans -from a sociologically situated 'rights-based' perspective. This approach considers migrants' attitudes towards specific 'civic integration' measures in a medium-term time frame, as well as in the new context created by the UK's vote to leave the EU. Based on the quantitative analysis of origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 24 publications
7
78
1
4
Order By: Relevance
“…We thus concur with McGhee et al. 's () observation that civic integration practices do not necessarily signal an intention to settle permanently. While trying to secure their settlement by consolidating their legal rights, families are simultaneously changing their outlook on the future.…”
Section: Processes Of Transnational Emplacement Among Eu Familiessupporting
confidence: 91%
See 1 more Smart Citation
“…We thus concur with McGhee et al. 's () observation that civic integration practices do not necessarily signal an intention to settle permanently. While trying to secure their settlement by consolidating their legal rights, families are simultaneously changing their outlook on the future.…”
Section: Processes Of Transnational Emplacement Among Eu Familiessupporting
confidence: 91%
“…The latest practices included the acquisition of settlement rights through permanent residency and subsequently naturalization aiming to mitigate the insecurities prompted by Brexit. This echoes the "undeliberate determinacy" pursued by Polish migrants (McGhee et al, 2017). These practices, however, divides our participants and are much debated at every social gathering.…”
Section: Processes Of Transnational Emplacement Among Eu Familiesmentioning
confidence: 86%
“…Looking to the future, Moreh et al (, p. 4) predict that naturalisation rates will increase as many EU migrants in the United Kingdom will want to acquire British passports. Similarly, from a survey of 894 Polish migrants in Britain, McGhee, Moreh, and Vlachantoni () found that 72% were aiming to settle in the United Kingdom in the next 5 years, thereby emphasising their national—U.K.—residential claims over their EU rights of free movement. For others, their solution to Brexit was to envisage their own exit, either by returning to their home countries (which many had flexibly envisaged anyway, sooner or later) or by moving elsewhere within Europe to countries where the rights of free movement, work, and residence seem more secure.…”
Section: Resultsmentioning
confidence: 99%
“…Sue and Ritter ), social media in particular has been identified as an increasingly useful platform for accessing migrant networks (cf. Dekker and Engbersen ), and the adopted strategy of ‘appropriate targeting’ has proved effective at reducing biases and increasing the representativeness of our sample (see McGhee, Moreh and Vlachantoni , where we compare our sample to that of the Annual Population Survey). In the context of our present analysis, the most important cautionary note in respect to the latter is that our sample will reflect more closely the attitudes of women, those of working age and the economically active.…”
Section: Methodsmentioning
confidence: 99%